2017
DOI: 10.1007/s00284-017-1301-3
|View full text |Cite
|
Sign up to set email alerts
|

Mink (Mustela vison) Gut Microbial Communities from Northeast China and Its Internal Relationship with Gender and Food Additives

Abstract: It is well documented that the microbial interactions and biodiversity play an important role in health and disease in mammalian species. There is a rare study about gut microbiota of Mustelidae family. In this study, 40 male and female minks from Northeast China were divided into three groups and fed until they reached maturity. The V3 region of 16S rRNA genes was amplified and sequenced using NGS. There were 526 OTUs principally concentrated among five bacterial phyla. Two points about mink's body weight gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…In a fecal microbiome study conducted on samples from mink in Northeast China, Zhao et al. () showed that the two most prevalent bacterial genera were Clostridium and Escherichia , phages, both of which were found in our study. Interestingly, significantly higher numbers of Pseudomonas ‐associated phage sequences were detected in adult female fecal samples compared to kit samples ( q = 0.02), but since the detected sequences may not represent colonization by Pseudomonas species, the implications of these results remain unclear.…”
Section: Discussionsupporting
confidence: 68%
“…In a fecal microbiome study conducted on samples from mink in Northeast China, Zhao et al. () showed that the two most prevalent bacterial genera were Clostridium and Escherichia , phages, both of which were found in our study. Interestingly, significantly higher numbers of Pseudomonas ‐associated phage sequences were detected in adult female fecal samples compared to kit samples ( q = 0.02), but since the detected sequences may not represent colonization by Pseudomonas species, the implications of these results remain unclear.…”
Section: Discussionsupporting
confidence: 68%
“…However, Firmicutes is followed by a much larger proportion of Proteobacteria than has been previously reported in healthy dogs, cats, and other carnivores (34% vs <15%) [ 7 9 , 28 33 ]. This is consistent with the high relative abundance of both Firmicutes and Proteobacteria found in mink feces by Bahl et al ., but unlike the work of Zhao et al ., in which a higher overall relative abundance of Proteobacteria was seen in mink feces, although the latter used a different methodology (amplification of the V3 region), which may explain, at least in part, the lack of agreement between studies [ 15 , 34 ]. As seen in other mammals, when the microbiota is compared between adults and young weaned animals [ 35 39 ], there were few significant differences identified between adult female mink and weaned kits.…”
Section: Discussionmentioning
confidence: 99%
“…Our study groups were suckling mink kits which had not been introduced to solid feed, and therefore their composition of gut bacteria was expected to be not so diverse and to differ from adult minks since the development of the bacterial microbiota is dependent on age and type of feeding [23,25]. Our results showed that the major groups of bacteria in both healthy and diseased animals were enterococci and staphylococci which differ from the composition in adult mink where Clostridia, Fusobacteria and Gammaproteobacteria dominate [27][28][29]48]. Large differences between the pools were seen and seem to correlate with litter age (Figs 2 and 3).…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, the combination of increased proportion of enterococci and E.coli that we found in the diarrheic group also has been demonstrated in piglets with New Neonatal Porcine Diarrhea (NNPD) [32,52,54], suggesting some similarities in pathology between mink kits and piglets with diarrhea in the suckling period. Clostridia and Escherichia-Shigella are major components of the adult bacterial microbiota [27,29], and based on these findings PWD in mink kits may be interpreted as a general result of less tolerance of too early colonization by specific bacteria groups. Material for this study was collected from commercial mink farms with severe on-going outbreaks of PWD and therefore it was impossible to control and avoid antimicrobial treatment of the females in all the sampled litters.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation